A COMPARISON OF SPEAKING SKILL BETWEEN JAVANESE L1 STUDENTS AND MADURA L1 STUDENTS AT 8TH D GRADE OF MTS NU TMI PUJON - Yulia Ratnawati (UIBU, 2018)
Language is one of the ways we express what in our mind is and through language we can communicate with others in our society. Based on the researcher observation at MTs NU TMI Pujon, the researcher can presume that the students of MTs NU TMI Pujon some of them has Javanese language as their mother tongue and others has Madura language as their mother tongue and they have different ability in speaking English as foreign language. Based on the test given by the researcher to some students at eight D class and analyze the data by using descriptive qualitative method, the researcher found some data. First, the researcher found that there are some differences between Javanese and Madura L1 students such as Madura L1 students got higher score in pronunciation and body language criteria, and also got higher average for all of criteria. Second, based on the data the researcher can conclude that 1ST language or mother tongue influence the students’ English speaking skill. Because, Madura language known as language that has stressing tone and intonation and most of Madura speak loudly and confidently. It makes Madura L1 students got higher score than Javanese.